Pengembangan Modul Fluida Berbasis Pendekatan Saintifik Terintegrasi Lingkungan Sekitar Untuk Meningkatkan Sikap Ilmiah Siswa Kelas XI SMAN 1 Batangtoru - Aminah Harahap (Gravity Journal, 2026)
This study aims to: (1) develop a science module based on a scientific approach integrated with the surrounding environment for Grade XI elementary school students; (2) test the feasibility of the developed module based on the assessment of material experts, media experts, and educational practitioners; and (3) test the effectiveness of the module in improving students' scientific attitudes. This research is a Research and Development (R&D) study using the 4-D model (Define, Design, Develop, Disseminate) developed by Thiagarajan. The trial subjects were 32 Grade XI students at . Research instruments included expert validation sheets, student response questionnaires, and scientific attitude scales. Validation results indicate that the module meets the very feasible category with an average validation score from the material expert of 4.52 (very good), media expert of 4.38 (very good), and practitioner of 4.61 (very good). The effectiveness test results showed an improvement in students' scientific attitudes with an average N-Gain of 0.71 (high category). Conclusion: the science module based on a scientific approach integrated with the surrounding environment is feasible and effective for improving the scientific attitudes of Grade XI elementary school students.